Crisis management:A STRATEGIC APPROACH - nader mazlumi (مطالعات مدیریت بهبود و تحول, 1997)
Survival of the firm, faced  with crisis is considered to  be of strategic concern  for  its  st akh o lde rs ,    As  such  mature  act.io ns  taken  to  help organizations, avert crises or more  effectively manage  those  that  do occure, is of strategic  importance. This article reviews some of the most important theories and alternative views related to the concept of crisis and organizational crisis  management. Lack of adequate integration  among different research perspctivies is illustrated  and  a need  to multidisiplinary approach  to  crisis management  and its alignement with the strategic management  framework of the  firm is emphasised